Efficacy of High Temporal Frequency Photoacoustic Guidance of Laser Ablation Procedures. (May 2021) - Yan, Yan; John, Samuel; Meiliute, Jurgita; Kabbani, Loay; Mehrmohammadi, Mohammad
Inaccurate placement of the ablation catheter and the inability to monitor the real-time temperature within the tissue of interest such as veins curbs the treatment efficacy of laser ablation procedures during thermal therapies. Our previous studies have validated the efficacy of photoacoustic (PA) imaging during endovenous laser ablation (EVLA) procedures. However, the PA-guided therapies suffer from low temporal resolution, due to the low pulse repetition rates of pulsed lasers, which could cause a problem during fast catheter motion and rapid temperature changes. Herein, to enhance the accuracy and sensitivity for tracking the ablation catheter tip and temperature monitoring, we proposed to develop a high frame rate (500 Hz), combined ultrasound (US), and PA-guided ablation system. The proposed PA-guided ablation system was evaluated in a set of ex vivo tissue studies. The developed system provides a 2 ms temporal resolution for tracking and monitoring the ablation catheter tip's location and temperature, which is 50 times higher temporal resolution compared to the previously proposed 10 Hz system. The proposed system also provided more accurate feedback about the temperature variations during rapid temperature increments of 10°C per 250 ms. The co-registered US and PA images have an imaging resolution of about 200 μm and a field of view of 45 × 40 mm 2 . Tracking the ablation catheter tip in an excised tissue layer shows higher accuracy during a relatively fast catheter motion (0.5–3 mm/s). The fast US/PA-guided ablation system will potentially enhance the outcome of ablation procedures by providing location and temperature feedback.